Are pharmacists on the front lines of the opioid epidemic? A cross-sectional study of the practices and competencies of community and hospital pharmacists in Punjab, Pakistan - Mubarak, Naeem; Zahid, Taheer; Rana, Fatima Rahman; Ijaz, Umm-E-Barirah; Shabbir, Afshan; Manzoor, Mahrukh; Khan, Nahan; Arif, Minahil; Mohd Zin, Che Suraya; Mahmood, Khalid; Asgher, Javaid; Elnaem, Mohamed Hassan (BMJ Publishing Group, 2023)
Introduction Countries are grappling with a rapidly worsening upsurge in the opioid-related overdose deaths, misuse and abuse. There is a dearth of data in Pakistan regarding the practices and competencies of pharmacists in handling opioid-related issues. Study design A cross-sectional study, conducted across Punjab, Pakistan. Method The study deployed a validated survey to evaluate the competencies and practices of the community and hospital pharmacists. Results 504 community pharmacists and 279 hospital pharmacists participated in the survey with an overall response rate of 85.5%. Almost half of the respondents ‘never’ or ‘sometimes’ made clinical notes in a journal or dispensing software to monitor ongoing opioid use. Generally, pharmacists were reluctant to collaborate with physicians or notify police regarding the abuse/misuse of opioids. Hospital pharmacists achieved significantly higher mean competency scores than chain and independent community pharmacists (p<0.05). In competency evaluation, three priority areas emerged that require additional training, that is, ‘opioid overdose management’, ‘opioid use monitoring’ and ‘therapeutic uses of opioids’. Conclusion Both community and hospital pharmacists hold significant positions and potential to contribute meaningfully to the mitigation of harms and risks associated with opioids. Nevertheless, this study underscores notable deficiencies in the competence of pharmacists, whether in hospital or community settings in Punjab, concerning various aspects related to the dispensing and utilisation of opioids. It also highlights the pressing need for the development of strategies aimed at improving several practice areas including the documentation, the quality of patient counselling, the effectiveness of reporting mechanisms for opioid abuse and the stringent enforcement of regulatory policies to curtail opioid misuse. Thus, to mitigate the opioid epidemic in Pakistan, it is imperative to institute opioid stewardship initiatives aimed at rectifying the competency and procedural deficiencies within the pharmacist workforce